Organization of the military pedagogical process in the military universities of the Republic of Kazakhstan - Умаров, Асхат (Pedagogy and Psychology, 2021)
The article discusses the issues of training professional personnel for the Armed Forces of the Republic of Kazakhstan, provides the current state of military education at all levels, provides data on existing military educational institutions of secondary, higher, postgraduate and additional education. The author made an attempt to briefly analyze the existing Kazakh and Russian studies on the topic of the article over the past five years. The review of dissertation research includes issues of the history of the training of military specialists in the Republic of Kazakhstan, problematic issues of military education, the formation of cadets’ readiness for military service and the development of the necessary professional competencies, patriotic education, the organization of the military pedagogical process, etc. Based on the analysis, the author concludes that there is a need for further modernization of the military pedagogical process in Kazakh military universities, the introduction of new educational technologies, an increase in the digital literacy of the teaching staff and the expansion of international cooperation.